Desymmetrization of an Octahedral Coordination Complex Inside a Self‐Assembled Exoskeleton. Issue 31 (21st June 2016) - Johnstone, Mark D.; Schwarze, Eike K.; Ahrens, Jennifer; Schwarzer, Dirk; Holstein, Julian J.; Dittrich, Birger; Pfeffer, Frederick M.; Clever, Guido H.
Abstract: The synthesis of a centrally functionalized, ribbon‐shaped [ 6 ]polynorbornane ligandL that self‐assembles with Pd II cations into a Pd2 L 4 coordination cage is reported. The shape‐persistent Pd2 L 4 cage contains two axial cationic centers and an array of four equatorial H‐bond donors pointing directly towards the center of the cavity. This precisely defined supramolecular environment is complementary to the geometry of classic octahedral complexes [M(XY)6 ] with six diatomic ligands. Very strong binding of [Pt(CN)6 ] 2− to the cage was observed, with the structure of the host–guest complex {[Pt(CN)6 ]@Pd2 L4 } supported by NMR spectroscopy, MS, and X‐ray data. The self‐assembled shell imprints its geometry on the encapsulated guest, and desymmetrization of the octahedral platinum species by the influence of the D 4 h ‐symmetric second coordination sphere was evidenced by IR spectroscopy. [Fe(CN)6 ] 3− and square‐planar [Pt(CN)4 ] 2− were strongly bound. Smaller octahedral anions such as [SiF6 ] 2−, neutral carbonyl complexes ([M(CO)6 ]; M=Cr, Mo, W) and the linear [Ag(CN)2 ] − anion were only weakly bound, showing that both size and charge match are key factors for high‐affinity binding. Abstract : Wear what suits you : A self‐assembled Pd2 L 4 4+ coordination cage featuring two axial cations and four equatorial H‐bond donors is able to bind octahedral complexes such as [Fe(CN)6 ] 3−, [Pt(CN)6 ] 2−, and [M(CO)6 ] 0 (M=Cr, Mo, W). As a custom‐built second coordination sphere of D 4 h symmetry, the cage lowers the symmetry of the guests, as indicated by IR spectroscopy.